Designing and transforming yield-stress fluids. Issue 5 (October 2019) - Nelson, Arif Z.; Schweizer, Kenneth S.; Rauzan, Brittany M.; Nuzzo, Ralph G.; Vermant, Jan; Ewoldt, Randy H.
Highlights: Categorizes "design with" versus "design of" rheologically-complex materials. Considers "How many ways to get a yield-stress fluid?" Considers "Can we predict properties from formulation and structure?" Considers "How to transform a yield-stress fluid to be more useful?" Future research directions are suggested to build the toolbox of design. Abstract: We review progress in designing and transforming multi-functional yield-stress fluids and give a perspective on the current state of knowledge that supports each step in the design process. We focus mainly on the rheological properties that make yield-stress fluids so useful and the trade-offs which need to be considered when working with these materials. Thinking in terms of "design with" and "design of" yield-stress fluids motivates how we can organize our scientific understanding of this field. "Design with" involves identification of rheological property requirements independent of the chemical formulation, e.g. for 3D direct-write printing which needs to accommodate a wide range of chemistry and material structures. "Design of" includes microstructural considerations: conceptual models relating formulation to properties, quantitative models of formulation-structure-property relations, and chemical transformation strategies for converting effective yield-stress fluids to be more useful solid engineering materials. Future research directions are suggested at the intersection of chemistry, soft-matter physics, and material science in the context of our desire to design useful rheologically-complex functional materials.